Hubungan Antara Persepsi Pola Asuh Permisif Orangtua Dengan Intensi Merokok Pada Remaja Awal - Maulida, Azizah; Dr. Wiwien Dinar Pratisti, M.Si, Psi, Dr. Wiwien Dinar Pratisti, M.Si, Psi (2016)
The aims of this study are to find: 1) The relationship between perception of permissive parenting with smoking intention in early adolescence. 2) Effective contribution of perceptions permissive parenting with smoking intention. 3) Perception of permissive parenting. 4) Smoking intention in early adolescence. The study leads to an hypothesis, that there is a positive relationship between perception of permissive parents with smoking intention in early adolescence. Subjects in the study are 120 peoples. While the population in this study is adolescence males aged 12-15 years in the district of Pasar Kliwon Surakarta. The measuring instruments used in this study were: a) Perception scala permissive parenting and b) Scale smoking intention. Data analysis techniques used in this study was the product moment correlation. Results of the analyst is consistent with the hypothesis, there is a significant positive relationship between perception of permissive parents with smoking intention in early adolescence in the district of Pasar Kliwon Surakarta. The higher the perception of permissive parents, the higher smoking intention in early adolescence, conversely the lower of the perception of permissive parents the lower smoking intention in early adolescence. This is was proved by the value of r(xy) of 0.616; sig. 0,000; (p<0.01). Effective contribution perception of permissive parents amounted to 37,95%. It is still 62,05% of other variables that might affect the smoking intention and of outside variable perception of permissive parents.